Linguistic Adaptation and Validation of the Academic Procrastination Scale – Short Version (APS-S) - Alegre Bravo, Alberto (2022)
This study was aimed at linguistically adapting the short version of McClosky's Academic Procrastination Scale (APS-S) and obtaining evidence of validity, reliability, and equity in university students from Lima. A total of 4,534 students participated, 2,052 women (45.3%) and 2,482 men (54.7%). The confirmatory factorial analysis of the scale reached an adequate fit to the hypothesized measurement model (CFI = .994, TLI = .988, RMSEA = .038, SRMR = .014). In addition, validity is evidenced with other variables, through correlations with academic self-efficacy (r=-.319; p<0.001) and academic performance (r= - .146; p < .001). Reliability was estimated with the ordinal alpha (αord = .867), and ordinal omega (ωord= .849) coefficients. Factor invariance analysis showed that the measure is equivalent between men and women (∆CFI < .010, ∆RMSEA < .015). It is concluded that the APS-S linguistically adapted to Spanish has psychometric properties, constituting a correct measure to evaluate procrastination in university students from Lima.